Photobiomodulation promotes repair following spinal cord injury by restoring neuronal mitochondrial bioenergetics via AMPK/PGC-1α/TFAM pathway - Zhu, Zhijie; Wang, Xuankang; Song, Zhiwen; Zuo, Xiaoshuang; Ma, Yangguang; Zhang, Zhihao; Ju, Cheng; Liang, Zhuowen; Li, Kun; Hu, Xueyu; Wang, Zhe (Frontiers in Pharmacology, 2022)
Background: Insufficient neuronal mitochondrial bioenergetics supply occurs after spinal cord injury (SCI), leading to neuronal apoptosis and impaired motor function. Previous reports have shown that photobiomodulation (PBM) could reduce neuronal apoptosis and promote functional recovery, but the underlying mechanism remains unclear. Therefore, we aimed to investigate whether PBM improved prognosis by promoting neuronal mitochondrial bioenergetics after SCI. Methods: Sprague Dawley rats were randomly divided into 4 groups: a Sham group, an SCI group, an SCI+PBM group and an SCI+PBM+Compound C group. After SCI model was established, PBM and Compound C (an AMPK inhibitor) injection were carried out. The level of neuron apoptosis, the recovery of motor function and mitochondrial function were observed at different times (7,14,28 days). The AMPK/PGC-1/TFAM pathway was hypothesized to be a potential target through which PBM could affect neuronal mitochondrial bioenergetics. In vitro, ventral spinal cord 4.1 (VSC4.1) cells were irradiated with PBM and cotreated with Compound C after oxygen and glucose deprivation (OGD). Results: PBM promoted the recovery of mitochondrial respiratory chain complex activity, increased ATP production, alleviated neuronal apoptosis and reversed motor dysfunction after SCI. The activation of the AMPK/PGC-1/TFAM pathway after SCI were facilitated by PBM but inhabited by Compound C. Equally important, PBM could inhibit OGD-induced VSC4.1 cell apoptosis by increasing ATP production whereas these changes could be abolished by Compound C. Conclusion: PBM activated AMPK/PGC-1/TFAM pathway to restore mitochondrial bioenergetics and exerted neuroprotective effects after SCI.